ANALISIS REAKSI PASAR MODAL INDONESIA TERHADAP KRISIS FINANSIAL GLOBAL (STUDI KASUS CHINA’S BLACK MONDAY) - Pondaag, Gracia R. M.; Mangantar, Maryam M.; Tasik, Hizkia H. D. (FEB Universitas Sam Ratulangi Manado, 2020)
Abstract: This research is an empirical study that aims to analyze whether there are differences in abnormal return and trading volume activity with the occurrence of global financial crisis (China’s black Monday) from various industry sector companies incorporated in the Indonesia Stock Exchange (IDX). This study uses event study methods and statistical analysis tools paired sample t-test. August 24, 2015 was chosen as the date of the event (event date) and the observation window for 29 days consisted of 14 days before the event date and 14 days after the event date. The sample in this study consisted of 40 companies of various industrial sectors which are members of the Indonesia Stock Exchange (IDX). The results showed that China’s Black Monday made a difference to the abnormal return and trading volume activity before and after the event.Keywords : Abnormal Return, Trading Volume Activity